Impact of Obesity With Chronic Hypertension In Pregnancy Age 35 Years - Triayuningsasi, Nila; Sa’diyah, Halimatus; Yulianingsih, Hera (Universitas Muhammadiyah Surabaya, 2025)
The incidence of pregnancy with obesity in Indonesia reaches 21.8%. This can be more serious, if the pregnant woman is too old (≥ 35 years) then there will be more complications for the mother and fetus. This case study was written based on midwifery management, in the form of subjective, objective documentation, analysis, and management. Based on a case study conducted on GIP0A0 ​​gestational age 36 weeks, 35 years old with obesity and old age. The impact of obesity found is chronic hypertension which will reduce the supply of oxygen and food from the mother to the baby so that the fetus is diagnosed with suspected Intrauterine Growth Restriction (IUGR). The mother is categorized as level II obese, obesity increases the risk of narrowing of the blood vessels by the accumulation of fat, which causes poor blood circulation which transports O2 and nutrients to the baby so that the fetus's weight does not match the gestational age, what is detected from TFU does not match the gestational age, in fact, accompanied by minimal amniotic conditions (oligohydramnios). To prevent complications for the mother and baby, delivery is carried out by cesarean section (SC). The mother's baby was a High Social Value Baby (HSVB), and after SC there was no success in providing exclusive breastfeeding, due to the mother's lack of knowledge about how and the benefits of breastfeeding. The mother chose IUD contraception which was inserted at the time of delivery. In conclusion, appropriate care provided by midwives during pregnancy, childbirth, newborns, postpartum and family planning is very important for the health of mothers and babies. So that early detection of risk factors can be minimized and possible complications can be prevented.